MINIATURE CYCLES FOR PIANO IN THE ARTISTIC CREATION OF SOLOMON LOBEL - ROMAN RUSLANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2017)
This article refers to the piano works of composer Solomon Lobel. Special attention is paid to the analysis of the composer’s cycles of miniatures for piano. The composer set himself the goal to valorize these cycles and to determine the unifying factors of the cycles written by composer Solomon Lobel.